Gender equity within medical specialties of Australia and New Zealand: cardiology's outlier status. Issue 4 (8th April 2020) - Burgess, Sonya; Shaw, Elizabeth; Ellenberger, Katherine A.; Segan, Louise; Castles, Anastasia V.; Biswas, Sinjini; Thomas, Liza; Zaman, Sarah
Abstract: Background: Gender disparity remains a prominent medical workforce issue, extending beyond surgical specialties with low proportions of female doctors. Aims: To examine female representation within Australia and New Zealand (NZ) among physician specialties and certain comparator surgical specialties with a focus on cardiology as an outlier of workforce gender equality. Methods: Data of practising medical specialists, new consultants and trainees were sought from the Australian Health Practitioner Regulation Agency, the Medical Council of NZ and the Royal Australasian College of Surgeons (2015–2017). The stratified data pertaining to interventional cardiologists were obtained through direct contact with individual hospitals (from 2017 to 2018) and derived from state‐based cardiac registries. Results: In Australia and NZ, there were fewer female practising adult medicine physician consultants ( n = 8956, 32%, P < 0.001), with gender disparities seen across most physician specialties. Cardiology (15%) was the only physician specialty with <20% representation; gastroenterology (23%), neurology (27%) and respiratory medicine (29%) had <30% female representation at the consultant level. The rates of cardiology (15%) and interventional cardiology (5%) were similar to general surgery (15%) and orthopaedics (4%). Although more than half of physician trainees are female, and most physician specialties are approaching or have equal gender ratios at the trainee level, cardiology (23%) and interventional cardiology (9%) remain significantly underrepresented. Conclusions: Cardiology is the only physician specialty with <20% female consultants, and this disparity is reflected throughout every stage of the cardiology training programme. Increased awareness and proactive strategies are needed to improve gender disparity within this underrepresented medical specialty.